Agranulocytosis and secondary infection related to JAK inhibitors and IL-6 receptor blockers: a disproportionality analysis using the US Food and drug administration adverse event reporting system - Wei, Chunyan; Yin, Wanhong; Hu, Tingting; Zhang, Jingyi; Dan, Huifang; Wu, Bin (Frontiers in Pharmacology, 2024)
Background: Given that theAs humanity's fight against coronavirus disease 2019 (COVID-19) is not over, we. We aimed to explore the occurrence of agranulocytosis and infectiousinfection complications in patients with COVID-19 and without non-COVID-19 following immunoregulatory therapy based on real-world data.Methods: This was a retrospective disproportionality analysis based on the US Food and Drug Administration Adverse Event Reporting System (FAERS). All cases reported between the first quarter of 2004 and the fourth quarter of 2022 about Janusjanus kinase inhibitors (baricitinib, tofacitinib, ruxolitinib) and interleukin-6 receptor blockers (tocilizumab, sarilumab) were collected. Disproportionality analyses were conducted by reporting odds ratio (ROR) and information component (IC).